2003
DOI: 10.1007/s00442-002-1105-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fertilisation on phenol content and growth rate of Cladina stellaris: a test of the carbon-nutrient balance hypothesis

Abstract: Responses of concentrations of usnic (UA) and perlatolic (PA) acids and the relative growth rate (RGR) of a mat-forming lichen, Cladina stellaris, to enhanced N and P input were studied in a fertilisation experiment. It was predicted on the basis of carbon-nutrient balance (CNB) hypothesis that the concentrations of these phenolics would decline and the growth rate increase in response to increased nutrient uptake. The concentration of UA showed a convex response pattern to increased N input whereas the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…Hence, this species doubled its annual biomass after a single 20-min immersion in a phosphorus solution suggesting that phosphorus is an important stimulant to growth. Growth of the fruticose lichen Cladonia stellaris (Opiz) Brodo was studied in relation to levels of fertilisation, and growth not responding to nutrient additions suggesting that some fruticose species may not respond to short-term changes in the availability of nutrients (Hyvarinen et al 2003). In a further study of C. stellaris, Makkonen et al (2007) found that both nitrogen and phosphate could limit the growth of fruticose lichens with phosphate having a greater effect than nitrogen.…”
Section: Nitrogen and Phosphorusmentioning
confidence: 99%
“…Hence, this species doubled its annual biomass after a single 20-min immersion in a phosphorus solution suggesting that phosphorus is an important stimulant to growth. Growth of the fruticose lichen Cladonia stellaris (Opiz) Brodo was studied in relation to levels of fertilisation, and growth not responding to nutrient additions suggesting that some fruticose species may not respond to short-term changes in the availability of nutrients (Hyvarinen et al 2003). In a further study of C. stellaris, Makkonen et al (2007) found that both nitrogen and phosphate could limit the growth of fruticose lichens with phosphate having a greater effect than nitrogen.…”
Section: Nitrogen and Phosphorusmentioning
confidence: 99%
“…Reindeer avoidance of lichens in fertilized forest stands may be caused by the presence of breakdown products of fertilizers in the ground, in the air close to the ground, or in air diffusing through the snow pack. Furthermore, nitrogen fertilization affects the amounts of the lichen compounds usnic and perlatolic acid (Hyvärinen et al 2003), and this can alter the taste of lichens and make them less palatable to reindeer. The results of fertilization trials by Å hman and Å hman (1984) have, however, shown that the concentrations of nitrate in fertilized lichens are significantly below the level that could be considered injurious to reindeer.…”
Section: Forest Fertilizationmentioning
confidence: 99%
“…Th ey concluded that internal recycling of N improves N use effi ciency in lichens and is likely ecologically important in N-limited environments typical of the undisturbed arctic. Th ese and other studies have repeatedly shown a direct correlation between N application or N availability and concentrations of N in lichen thalli (Hahn et al 1993;Hyvärinen andCrittenden 1998a, 1998b;Hyvarinen et al 2003;Walker et al 2003;Weiss et al 2005). …”
Section: Community Level Responses Of Tundra Vegetationmentioning
confidence: 90%
“…Nitrogen, P, and N:P ratios infl uenced the proportion of the medullary layer volume occupied by the algal cells, the thallus volume occupied by the internal lumen, and the algal cell-wall area covered by fungal hyphae, indicating that ecologically realistic changes in the availability of key macronutrients can alter the growth of symbionts. Hyvärinen et al (2003) showed that a moderate N treatment (3 kg ha -1 against a background of 0.5 kg ha -1 wet deposition in 3 months) lowered usnic acid (C 18 H 16 O 7 ) concentrations in the star reindeer lichen with and without P application; P alone increased usnic acid, and higher N (10 kg ha -1 ) had no eff ect on usnic acid. None of the treatments increased growth rate.…”
Section: Physiological and Chemical Responses Of Vegetationmentioning
confidence: 97%
See 1 more Smart Citation